Multi-analyte liquid biopsies for molecular pathway guided personalized treatment selection in advanced refractory cancers: A clinical utility pilot study - Patil, Darshana; Akolkar, Dadasaheb; Nagarkar, Rajnish; Srivastava, Navin; Datta, Vineet; Patil, Sanket; Apurwa, Sachin; Srinivasan, Ajay; Datar, Rajan (Frontiers in Oncology, 2022)
Purpose: The selection of safe and efficacious anticancer regimens for treatment of broadly refractory patients with metastatic cancers remains a clinical challenge. Such patients are often fatigued by toxicities of prior failed treatments and may have no further viable standard of care treatment options. Liquid Biopsy-based multi-analyte profiling in peripheral blood can identify a majority of drug targets that can guide the selection of efficacious combination regimens. Patients and Methods: LIQUID IMPACT was a pilot clinical study where patients with advanced refractory cancers received combination anticancer treatment regimens based on multi-analyte liquid biopsy (MLB) profiling of circulating tumor biomarkers; this study design was based on the findings of prior feasibility analysis to determine the abundance of targetable variants in blood specimens from 1299 real-world cases of advanced refractory cancers. Results: Among the 29 patients in the intent to treat (ITT) cohort of the trial, 26 were finally evaluable as per study criteria out of whom 12 patients showed Partial Response (PR) indicating an Objective Response Rate (ORR) of 46.2% and 11 patients showed Stable Disease (SD) indicating the Disease Control Rate (DCR) to be 88.5%. The median Progression-Free Survival (mPFS) and median Overall Survival (mOS) were 4.3 months (95% CI: 3.0 – 5.6 months) and 8.8 months (95% CI: 7.0 – 10.7 months), respectively. Toxicities were manageable and there were no treatment-related deaths. Conclusion: The study findings suggest that MLB could be used to assist treatment selection in heavily pretreated patients with advanced refractory cancers.